Going into the groin: Injection into the femoral vein among people who inject drugs in three urban areas of England. (1st July 2015) - Hope, V.D.; Scott, J.; Cullen, K.J.; Parry, J.V.; Ncube, F.; Hickman, M.
Highlights: 53% reported ever groin (femoral vein) injecting; 41% in preceding month. The most common reasons were " Can't get a vein elsewhere ", "discreet " and " quicker ". Half first injected into the groin within 5-years of starting to inject. 1 in 10 started groin injecting at the same age that they started injecting. For some groin injecting may now be by choice, and not the last resort. Abstract: Background: There have been increasing concerns about injection into the femoral vein – groin injecting – among people who inject drugs in a number of countries, though most studies have been small. The extent, reasons and harms associated with groin injecting are examined. Method: Participants were recruited using respondent driven sampling (2006–2009). Weighted data was examined using bivariate analyses and logistic regression. Results: The mean age was 32 years; 25% were women ( N = 855). During the preceding 28 days, 94% had injected heroin and 13% shared needles/syringes. Overall, 53% reported ever groin injecting, with 9.8% first doing so at the same age as starting to inject. Common reasons given for groin injecting included: " Can't get a vein elsewhere " (68%); " It is discreet" (18%); and " It is quicker" (14%). During the preceding 28 days, 41% had groin injected, for 77% this was the only body area used (for these " It is discreet" w as more frequently given as a reason). In the multivariable analysis, groin injection was associated with: swabbing injection sites; saving filters for reuse; and receiving opiate substitution therapy. It was less common among those injecting into two body areas, and when other people (rather than services) were the main source of needles. Groin injection was more common among those with hepatitis C and reporting ever having deep vein thrombosis or septicaemia. Conclusions: Groin injection was common, often due to poor vascular access, but for some it was out of choice. Interventions are required to reduce injecting risk and this practice.